Comparative Study of Exceptions to Image Rights With Emphasis on the Iranian Legal System - Mirshekari , Abbas; Fattahi, Alireza; Saeidi, Neda (Journal of Legal Studies, 2023)
Individuals have a right to their images, meaning that they can decide on permitting having their photos taken or published. Therefore, the consent of the person who is the subject of an image must be obtained for photography or publication. This right, however, is not absolute and without exceptions. People have the right to know what is happening in their community. As a result, if a photo is taken of someone and published for information, it is not necessary to insist upon obtaining consent. Several legal systems allow the imaging of others for informational purposes. However, in such cases, the privacy and dignity of people must be observed, and no one is permitted to publish images insulting or contrary to the public/personal internet. Also, images must not be used for business purposes. In the Iranian legal system, the freedom of the press (principle 24 of the Constitution) and the importance of public interest and its priority over private interests (principle 40 of the Constitution) convey the same idea that the principle is to allow publishing images for informational purposes.